رابطه بین پیک فرکانس آلفا نواحی مختلف مغز با توجه و بازداری پاسخ شنیداری و دیداری. - سئودا عباسی; سمیه حیثیت طلب; زینب برزگر; حجت قیمتگر; محمد علی نظری (Medical Journal of Tabriz University of Medical Sciences, 2025)
Background. The alpha band has been extensively studied in relation to cognitive functions such as attention and inhibition, with alpha peak frequency considered a potential biomarker for these processes. However, more research is needed to better understand these associations. Methods. In this study, electroencephalography (EEG) data from a non-clinical sample of 632 elementary school children aged 6 to 11 years (251 girls and 381 boys) with a mean (±SD) age of 7.07 ± 1.499 years were recorded using 19 electrodes. The alpha peak frequency in open- and closed-eye conditions was calculated using fast Fourier transform. Attention and response inhibition were assessed through an integrated auditory and visual attention test. Results. Results revealed a significant positive correlation between alpha peak frequency and both auditory and visual attention in both open- and closed-eye conditions. Additionally, a negative correlation was observed between alpha frequency peak and reaction time in auditory and visual aspects. The shorter the reaction time, the faster the cognitive processing. However, the correlation with response inhibition was weaker. Conclusion. These findings confirm the key role of alpha peak frequency in attention and cognitive processing speed. The importance of brain activity recording conditions (eyes open and closed) and auditory and visual modalities was also confirmed in this research. Practical Implications. Alpha peak frequency can serve as a biomarker for assessing cognitive functions and offers valuable insights into brain activity during tasks with different sensory stimuli.